Nonlinear dynamic analysis of spindle system considering thermal-solid coupling - Wei, Yuan; Xu, Fanyi (Nonlinear dynamics, 2025)
During spindle operation, bearings play a supporting role and are subject to dynamic forces and thermal deformation, resulting in structural changes. The main spindle system’s thermal and dynamic properties will be impacted by the bearing structure alteration, and two influence each other with the existence of a coupling relationship. This paper considers thermal-solid coupling effect, studies influence of nonlinear characteristics on system, creates a spindle model and examines the system architecture. Subsequently, calculations are made for the spindle system heat production and transport, the temperature and deformation of system primary node are examined using the thermal network method, and the results are applied to the calculation of the bearing nonlinear restoring force and the motor unbalanced magnetic pulling force. In addition, considering spindle structure, the concentrated mass approach is used to create nonlinear dynamics analysis model for spindle, and the system model is solved to study its nonlinear dynamics behavior by the numerical method. Spindle system dynamic properties under various influencing variables, such as rotational speed, unbalanced mass, bearing stiffness, and so on, are finally examined, and the linear and nonlinear movements of the spindle system under various operating situations are observed, using bifurcation diagrams and frequency domain waterfall diagrams. This spindle model examines and discusses how system performance varies with different factors and thermal impacts, which can more clearly illustrate how temperature and other factors affect the system dynamic properties and serve as a useful design reference for the system. Graphical abstract